Systematization of Methodical Approaches on Evaluation of Efficiency of Innovative Projects (Economic journal of Lesya Ukrainka Volyn National University, 2018)
The article deals with the content of the concept «innovative project», the proposed classification of innovation projects. The model of an innovative project with risk taking is developed.The peculiarities of evaluation of innovative projects were studied and recommendations on the selection of indicators of efficiency of innovative projects were developed. Evaluating the cost-effectiveness of innovation projects is usually associated with some difficulties: a large number of partial indicators characterizes its own separate aspect of efficiency, complicates the evaluation and selection of effective and ineffective projects.To solve this problem, the author recommends using an integral indicator of economic efficiency that takes into account partial performance indicators of the innovation project stages and allows determining the overall level of economic efficiency based on the rating. The integral indicator greatly facilitates the evaluation and selection of innovative solutions, as well as the comparison between alternative approaches and the choice of the direction of capital investment by the enterprise.This will allow monitoring the dynamics of the main values of the innovation project: to investigate the dependence of the final results on management decisions and, accordingly, to distribute the limited financial resources rationally; respond timely to changes in the internal and external environment.
Keywords: innovation project, classification, efficiency, risk, indicators.